Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kepuasan Kerja di PT. Pelangi Mizan - Nurrohman, Muldan; Adiyanti, Siska Ayudia (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: Job satisfaction is a critical component in organizational effectiveness and employee retention, especially in creative industries such as publishing. This study explores how organizational culture and work environment affect job satisfaction at PT. Pelangi Mizan, a leading book publishing company in Bandung, Indonesia. Background Problems: The research addresses the problem of low job satisfaction potentially stemming from organizational culture and workplace conditions. The key research question is: To what extent do organizational culture and work environment influence job satisfaction among employees at PT. Pelangi Mizan?Novelty: While prior studies have examined similar variables in corporate settings, limited attention has been given to their impact within the Indonesian publishing sector. This study offers a fresh context and contributes to the literature by analyzing both physical and psychological workplace dimensions. Research Methods: Using a quantitative approach, the study surveyed 90 employees using validated questionnaires. Data were analyzed through multiple linear regression in SPSS 25 to test partial and simultaneous effects of the independent variables. Finding/Results: The findings indicate that both organizational culture and work environment significantly and positively influence job satisfaction, both individually and collectively. The combined effect explains approximately 54.6% of the variation in job satisfaction. Conclusion: The study concludes that fostering a strong organizational culture and maintaining a supportive work environment are key to enhancing employee satisfaction. These insights are valuable for HR practitioners in similar organizational contexts.